Heavy metal contamination of water and fish in peri-urban dams around Bulawayo, Zimbabwe. Issue 4 (14th December 2017) - Teta, C; Ncube, M; Naik, YS
Abstract : Urban effluents are significant sources of heavy metal pollution in fresh water. Metal contamination in dams around the city of Bulawayo, Zimbabwe, were monitored during October 2014 to assess ecological and public health risks. Heavy metals were measured in water, sediment and fish in dams located downstream of effluent discharge zones in Bulawayo and were compared to those in a pristine upstream dam. Water conductivity indicated pollution of downstream dams. Levels of lead (0.13–0.28 ppm) and cadmium (0.02–0.06 ppm) in water from downstream dams exceeded WHO safe limits for drinking water. Cadmium levels in polluted dams also exceeded the safe limit for agricultural use. Sediments of effluent-polluted dams had metal contamination factors ranging from 8.8 to 31.2 relative to the control, and fish from the dams had higher metal content and were unfit for human consumption. Metal levels were also measured along an urban stream to establish the sources of metals. The city's industrial zone had the highest levels of metals, suggesting that industrial effluents were major sources of contamination. The environmental consequences and human health risks of the pollution of peri-urban water bodies from urban effluents are discussed.